An Application of audiovisual distraction to reduce pain in children with thalassemia and acute disease - Halimah Halimah; Reta Renylda (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Background: Pain during invasive procedures is an unpleasant thing experienced by all children when hospitalized, including children with acute illnesses or chronic diseases such as thalassemia. Nurses need to implement interventions from atraumatic care to reduce the pain felt by children, such as by providing audiovisual distraction techniques. This study aimed to see the difference in pain felt by thalassemia and non-thalassemia children after being given an audiovisual distraction technique intervention. Methods: This study uses a quasi-experimental method by comparing the pain of thalassemia children with non-thalassemia children aged 1-12 years after being given audiovisual distraction techniques. The data collection period was from May to August 2022 on 33 children (15 thalassemia children and 18 non-thalassemia children) using purposive sampling techniques from 3 hospitals in Jambi. Results: Thalassemia children felt no significant difference in pain compared to non-thalassemia children who were given audiovisual distraction techniques. Conclusion: All children feel pain even though children with chronic diseases have repeated hospitalization experiences, so it is important to provide nursing interventions for pain management, especially in children with chronic conditions (thalassemia), to prevent further effects of recurrent pain felt by children.